ChemInform Abstract: Amides in One Pot from Carboxylic Acids and Amines via Sulfinylamides. Issue 25 (24th June 2014) - Bai, Jianfei; Zambron, Bartosz K.; Vogel, Pierre
Abstract This efficient method is applicable to primary and secondary amines, including the tert‐butyl esters of α‐amino acids.